2015
DOI: 10.1517/14728222.2014.978860
|View full text |Cite
|
Sign up to set email alerts
|

The SIX1-EYA transcriptional complex as a therapeutic target in cancer

Abstract: Introduction The SIX homeodomain proteins and the EYA family of co-activators form a bipartite transcription factor complex that promotes the proliferation and survival of progenitor cells during organogenesis and is down-regulated in most adult tissues. Abnormal over-expression of SIX1 and EYA in adult tissue is associated with the initiation and progression of diverse tumor types. Importantly, SIX1 and EYA are often co-overexpressed in tumors, and the SIX1-EYA2 interaction has been shown to be critical for m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
115
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 86 publications
(120 citation statements)
references
References 114 publications
(187 reference statements)
5
115
0
Order By: Relevance
“…To determine whether EYA4 could bind to the p27Kip1 promoter in chromatin, a chromatin immunoprecipitation (ChIP) analysis was performed in U87MG cells. It has been reported that EYA protein can't directly bind to DNA, and it usually acts as a co-factor for the Six family proteins, which are transcription factors binding to DNA directly [8,27]. We found a putative Six1-binding site (GGGTATCA) in the promoter region of the p27Kip1 gene, at -1670 from the transcription star site.…”
Section: Eya4 Suppresses the Expression Of P27kip1 In Gliomamentioning
confidence: 77%
“…To determine whether EYA4 could bind to the p27Kip1 promoter in chromatin, a chromatin immunoprecipitation (ChIP) analysis was performed in U87MG cells. It has been reported that EYA protein can't directly bind to DNA, and it usually acts as a co-factor for the Six family proteins, which are transcription factors binding to DNA directly [8,27]. We found a putative Six1-binding site (GGGTATCA) in the promoter region of the p27Kip1 gene, at -1670 from the transcription star site.…”
Section: Eya4 Suppresses the Expression Of P27kip1 In Gliomamentioning
confidence: 77%
“…SIX1 overexpression is observed in a number of primary human cancers, where it is associated with recurrence, metastasis, resistance to standard chemotherapeutic agents, and decreased patient survival (22, 23, 2933). Our findings in the mouse suggested that aberrant SIX1 expression could have a role in human endometrial cancer, but to date there are no published reports that have addressed this question.…”
Section: Resultsmentioning
confidence: 99%
“…SIX1 is a homeodomain-containing transcription factor that plays essential roles in mouse organogenesis by regulating cell proliferation, survival, migration, and invasion (21, 22). Indeed, it is considered an oncofetal protein because dysregulation and inappropriate re-expression result in genomic instability, malignant transformation, and metastasis in animal models and humans (2123). Neonatal exposure to estrogenic chemicals not only causes a dramatic increase in Six1 transcript expression in the mouse uterus, but it also causes Six1 expression to become estrogen-responsive (19, 20).…”
Section: Introductionmentioning
confidence: 99%
“…Six1 expression is low or undetectable in most differentiated tissues, yet numerous studies have demonstrated elevated expression in tumors of multiple origins, where it is linked to metastatic disease. 3 Its pro-oncogenic functions include regulation of proliferation, survival, stem/progenitor cell functions, and in carcinomas, epithelial to mesenchymal transitions (EMT), 4 therefore closely mimicking its developmental roles.…”
mentioning
confidence: 99%
“…Six1 expression results in decreased differentiation and an increase and/or maintenance of stem/progenitor cell populations in multiple tissue types. 4 Indeed, overexpression of a pool of 8 genes including Six1, Six2, and the Six1 co-activator, Eya1, reprograms adult cells to embryonic nephron progenitors. 6 In contrast, increased p53 has been strongly linked to a differentiated state.…”
mentioning
confidence: 99%